Rice-fish culture in the Mekong delta, Vietnam: constraint analysis and adaptive research - Rothuis, Arijo (Katholieke University Leuven, 1998)
This study is a survey of agriculture practices and pest management strategies among rice and rice-fish farmers in the Mekong Delta. Based on an economic comparison between different farmer categories, it is argued that rice-fish farming provides a sustainable alternative to rice monoculture, if the farmer takes full advantage of the natural productivity of the rice field ecosystem. The aim should be to reduce the resource use, avoid overuse of agrochemicals and improve production efficiency through increased recycling of nutrients and matter